Transforming healthcare : a focus on consumerism and profitability - Hefner, Jennifer L.; Al-Amin, Mona. (Emerald Publishing Limited, 2020)
Shedding light on current transformations in payment mechanisms and transparency of hospital performance data and prices, this volume of Advances in Health Care Management presents findings on hospital profitability, cost, and organizational structures. Divided into two sections: 'Reimbursement, Cost and Profitability' and 'The Move Towards Transparency', the chapters employ a variety of research methodologies to explore the impact of transformation in payment and debt structures, profitability, and horizontal or vertical integration on outcomes such as price, clinical outcomes, and health plan selection. The authors examine recent changes including the redesign of the U.S. health care system to achieve higher value, and the establishment of mechanisms that transform reimbursement models and promote consumerism through transparency of data. Additionally, the volume takes a look at the emerging trend of transparency between health care stakeholders such as patients, health care staff, hospitals, insurance companies, and the government, providing a valuable insight into how the future might look.
Prelims -- Section I Reimbursement, Cost, and Profitability -- Bundled Payment Programs as an Application of Case Rate Provider Reimbursement -- Profitability of Rural Hospitals: An Analysis of Government Payment Policies -- Assessing the Impact of Privatization of Public Hospitals on Community Orientation: A Stakeholder Approach -- The Cost of Capital, Leverage, and System Membership: Does System Membership Help Hospitals Achieve Optimal Leverage? -- Section II The Move Towards Transparency -- When Is Medical Care Price Transparency a Good Thing (and When Isn't It)? -- Consumers' Exposure to Price Transparency: Compliance Testing and Sentiment Analysis of US Hospitals During 2019 -- Financial Literacy and Consumer Choice of Health Insurance: Evidence from Low-income Populations in the United States -- Does Transparency of Quality Metrics Affect Hospital Care Outcomes? A Systematic Review of the Literature -- Leadership and Safety Excellence: The Experience of Hospital Support Service Workers -- Outcome Warranties -- Index.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Medical economics; Medical -- General; Health economics